Mechanism of Dynamic Formation of Ultrafine Ferrite Grains during High Temperature Processing in Steel1 . Issue 3 (16th January 2017) - Zhao, Lijia; Park, Nokeun; Tian, Yanzhong; Shibata, Akinobu; Tsuji, Nobuhiro
Abstract : The grain refinement mechanism of ferrite dynamically transformed (DT) from austenite is investigated in a 10Ni–0.1C steel. For decades, it has been debated whether dynamic recrystallization (DRX) contributes to the grain refinement of DT ferrite. Here, the authors show that the role of DRX has been previously underestimated in grain refinement of ferrite and intrinsically it is the DRX that leads to ultra grain refinement of DT ferrite. The DT ferrite shows an unconventional grain growth behavior, that is, grain coarsening at an early stage of transformation with subsequent grain refinement by DRX, which strongly depends on the strain rate. The high strain concentration on fine ferrite grains within the austenite + ferrite structure produced by DT mainly contributes to the occurrence of DRX to form ultrafine‐grained ferrite structures. Abstract : Grain refinement mechanism of ferrite dynamically transformed (DT) from austenite is clarified. The study shows that the role of dynamic recrystallization (DRX) has been previously underestimated in grain refinement of ferrite and it is suggested that new thermomechanical processes should be developed by enhancing the DRX (of DT ferrite), which has a strong strain rate dependency.